2013
DOI: 10.1200/jco.2013.31.6_suppl.59
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II study of safety and efficacy of orteronel (TAK-700), an oral, investigational, nonsteroidal 17,20-lyase inhibitor, with docetaxel and prednisone (DP) in metastatic castration-resistant prostate cancer (mCRPC): Updated phase II results.

Abstract: 59 Background: Orteronel is an investigational non-steroidal, selective inhibitor of 17,20-lyase, a key enzyme in the production of steroidal hormones. DP is currently an approved therapy in mCRPC; this phase 1/2 study examined orteronel + DP in men with mCRPC. Methods: Castrate men (testosterone [T] <50 ng/dL) with mCRPC, no prior chemotherapy and no ketoconazole/abiraterone received orteronel (400 mg BID) + D (75 mg/m2 q3w) + P (5 mg BID). The primary phase 2 objectives were tolerability, PK, serum PSA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…A second phase I/II study (NCT01084655) was conducted to evaluate orteronel (200 mg or 400 mg given twice daily) in combination with docetaxel given every 3 weeks at 75 mg m −2 and prednisone 5 mg twice pre day, in patients with mCRPC 66. The combination was generally well-tolerated with no dose-limiting or unexpected toxicities reported.…”
Section: Inhibitors Of Androgen Synthesis In Developmentmentioning
confidence: 99%
“…A second phase I/II study (NCT01084655) was conducted to evaluate orteronel (200 mg or 400 mg given twice daily) in combination with docetaxel given every 3 weeks at 75 mg m −2 and prednisone 5 mg twice pre day, in patients with mCRPC 66. The combination was generally well-tolerated with no dose-limiting or unexpected toxicities reported.…”
Section: Inhibitors Of Androgen Synthesis In Developmentmentioning
confidence: 99%
“…Whether concomitant steroids would have prevented some of the AEs that led to discontinuation of therapy is unclear. Data from other orteronel trials in different patient populations and disease settings showed rates of discontinuation due to AEs of 42% in a phase II study of orteronel plus docetaxel and prednisone in 24 patients with chemotherapy-na€ ve mCRPC (26), 21% overall in a phase I/II study of orteronel with or without prednisone in 123 patients with mCRPC, in which the discontinuation rates due to AEs were similar between the 2 treatment groups (27), and 26% in a phase III study of orteronel plus prednisone in 734 patients with mCRPC that progressed post-docetaxel treatment (28).…”
Section: Discussionmentioning
confidence: 99%
“…Petrylak et al presented a Phase I study of docetaxel in combination with orteronel at the 2012 American Society of Clinical Oncology annual meeting [18]. In this study, orteronel was given b.i.d.…”
Section: Chemistrymentioning
confidence: 99%
“…plus docetaxel/prednisone [19]. The primary end points were: safety, pharmacokinetics and PSA response.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation